Sociodemography, Knowledge of Maternal Circumcision and Its Correlation to the Implementation of Baby Girl Circumcision in Securai Selatan Village, Babalan District, Langkat Regency - Rini Susanti; Sudarianti; Alfi Laili; Ruri Aditya Sari (Science Midwifery, 2022)
The practice of circumcision for girls has not been shown to be beneficial for health, but in Indonesia the practice of circumcision in girls still occurs mainly in some villages. Thus, this research is feasible and important to be carried out, with the aim of mapping the sociodemographic and maternal knowledge about the implementation of baby girl circumcision. The method of collecting data by distributing questionnaires to 80 mothers who performed circumcision on infant girls aged 0-11 years with purposive sampling. The data from the study were processed using validity, reliability tests and uni and multivariate tests to determine the correlation. This study shows that girls living in urban areas are more likely to be circumcised than children living in rural areas. Based on the results urban residents have better access to health services when compared to rural residents. This can be seen from the results of Riskesdas 2013 where health workers, while in rural areas only 40.6 percent circumcise 64.7 percent of women aged 0-11 years in urban areas. Thus, shamans or circumcisors (59.4%) circumcise most women in rural areas.